Fatty acid profile in cord blood of neonates born to optimally controlled gestational diabetes mellitus. (December 2016) - Léveillé, Pauline; Ardilouze, Jean-Luc; Pasquier, Jean-Charles; Deacon, Charles; Whittingstall, Kevin; Plourde, Mélanie
Abstract: Objective: To evaluate the fatty acid profile of cord blood phospholipids (PL), cholesteryl esters (CE), triglycerides (TG) and non-esterified fatty acids (NEFA) in neonates born to mothers with gestational diabetes mellitus (GDM) compared to non-diabetic mothers. Methods: The offspring of 30 pregnant women (15 non-diabetic controls, 15 with diet- or insulin-controlled GDM) were recruited before delivery. Cord blood was collected. After lipid extraction, PL, CE, TG and NEFA were separated by thin layer chromatography and analysed by gas chromatography. Results: In GDM vs. control mothers, maternal glycated haemoglobin (A1C, mean±SD) was not different between groups: 5.3±0.5% vs. 5.3±0.3% ( p =0.757), respectively. Cord plasma fatty acids were not different in TG, CE and NEFA between GDM and non-diabetic mothers. However, in PL, levels of palmitate, palmitoleate, oleate, vaccinate and di-homo-gamma-linolenate were significantly lower, with a trend for lower arachidonate ( p =0.078), in neonates born to GDM mothers compared to controls. Conclusion: In contrast to other studies on cord blood docosahexaenoic acid (DHA) levels in GDM mothers, we did not found lower levels of DHA in cord PL, CE, TG or NEFA in neonates born to GDM compared to non-diabetic mothers.